Cloning and detection of the antagonistic related genes of enterobacter cloacae B8 to Xanthomonas oryzae pv. oryzae with transposon tagging method - HUANG Hai-ning; YU Xu-ping; CHEN Wei-liang; GONG Hong-fei; LI De-bao (浙江大学学报. 农业与生命科学版)
Enterobacter cloacae B8, which was firstly isolated from the surface of rice leaves, is an antagonistic bacterium against Xanthomonas oryzae pv. oryzae and many other bacteria pathogens. For the understanding of the antagonistic mechanism of E. cloacae B8 against X. oryzae pv. oryzae, transposon tagging technique was adopted to clone antagonistic related genes of E. cloacae B8. Mediated with suicidal plasmid pZJ25, Tn5 transposed to the chromosome of B8, and resulted in the isolation of two strains named B8B and B8F, which lost the antagonistic character. Southern blot of EcoR I cut DNA of B8, B8B, B8F with Tn5 fragment as probe showed that there was a band about 20 kb or 9 kb in size in B8B and B8F respectively, but no band in B8. Genomic DNA of two mutated strains were isolated respectively, cut with BamH Ⅰ, ligated to BamHⅠ cut vector pBS. Using the Kan resistance of Tn5 fragment, two plasmids named pTLB and pTLF were isolated, and two DNA fragments of B and F with Tn5 about 6 kb and 7 kb were obtained. Southern blot of B8, B8B, B8F DNA with probe of total plasmid pTLB or 0.8 kb BamH Ⅰ + Hpa Ⅰ foreign DNA fragment of pTLF (the F fragment) showed that two DNA fragments around the transposition sites were cloned, which were in two different positions in B8 geonome.